FORMATION AND DEVELOPMENT OF THE COTTON GINNING INDUSTRY IN THE SURKHANDARYA OKRUG (FROM THE EARLY 20TH CENTURY TO THE 1940s) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the formation and development of the cotton ginning industry in the Surkhandarya region based on historical sources. It analyzes the construction of the first cotton ginning plant in Termiz in the early twentieth century, the role of local entrepreneurs—the Matchinboyev brothers—in its establishment, and the influence of the economic policy of the Russian Empire on the agriculture of the region. The study also highlights the establishment of cotton ginning plants in Denov, Sherobod, and Khazarbog, the construction of railways, and the expansion of the cotton ginning industry as a result of Soviet policies aimed at developing cotton cultivation. In addition, the article examines economic and organizational changes that occurred in the cotton sector during the 1920s–1940s.
Keywords: Surkhandarya, cotton growing, cotton ginning plant, Termiz plant, Matchinboyevs, Denov cotton plant, Khazarbog, Sherobod, railway, cotton industry, Soviet period, agriculture.